Deep Learning Dalam Perspektif Pendidikan Agama Kristen Untuk Membentuk Kemampuan Berpikir Kritis Siswa Kelas VIII di SMPN 89 Jakarta - Mara, Djeta; Siringo Ringo, Samuel; Messakh, Jacob (Peneliti.net, 2026)
This study aims to analyze the application of deep learning in the context of Christian Religious Education in shaping and building critical thinking skills in grade VIII students at SMPN 89 Jakarta. The background of this study focuses on the low critical thinking skills of students as seen from the lack of active participation, limitations in expressing opinions, and difficulties in understanding the material in depth. The method used in this study is qualitative descriptive, with data collection through observation, interviews, and documentation. The subjects studied included Christian Religious Education teachers and grade VIII students. Data analysis is carried out through several stages, namely data reduction, data presentation, and drawing conclusions. The results of the study show that the application of deep learning in Christian Religious Education has succeeded in increasing students' active involvement, encouraging reflective skills, and helping students in connecting the material with daily life. In addition, this approach has proven to be effective in honing critical thinking skills through an awareness, meaningful, and fun learning process. Therefore, the application of deep learning In Christian Religious Education has an important role in improving the quality of learning and forming. critical thinking skills in students, although it still requires optimization in its implementation.